Wireless Mobile Power Communication System Based on Artificial Intelligence Algorithm - Juan Du; Mingqi Guo (International Transactions on Electrical Energy Systems)
In order to solve the problems of low-risk assessment accuracy and long time-consuming assessment of current wireless mobile communication systems, a wireless mobile communication system based on artificial intelligence algorithms is proposed. First, the research status of risk assessment of wireless mobile communication system at home and abroad is analyzed, and the risk assessment index system of wireless mobile communication system is established; then, the learning samples are collected according to the risk assessment index system of wireless mobile communication system, and artificial intelligence algorithm is used to optimize the neural network. Build the wireless mobile communication system risk assessment model; finally, carry out the wireless mobile communication system risk assessment simulation comparison test. The experimental results show that the accuracy rate of the risk assessment of the wireless mobile communication system by the artificial intelligence algorithm is over 95%, and the assessment error is smaller than in other models. The risk assessment time of the wireless mobile communication system is significantly reduced, the real-time performance is better, and it has a higher practical application value.